Relationship between conversion of localized juvenile periodontitis-susceptible children from health to disease and Actinobacillus actinomycetemcomitans leukotoxin promoter structure - Bueno, L C; Mayer, M P; DiRienzo, J M (Journal of periodontology (1970), 1998)
The periodontal pathogen Actinobacillus actinomycetemcomitans produces a leukotoxin that is considered a primary virulence factor in localized juvenile periodontitis (LJP). Select strains of the bacterium contain a 530-bp deletion in the promoter region of the leukotoxin gene operon which results in enhanced transcription of the leukotoxin. DNA hybridization and polymerase chain reaction (PCR) were used to examine genetic variants of A. actinomycetemcomitans in 24 LJP-susceptible children from 21 families having a history of the disease and 34 control children from non-LJP families. A significant association was found between the detection of variants that had a deletion in the leukotoxin promoter region, indicative of a high level expression leukotoxin genotype, and conversion from a healthy periodontal status to disease. Subjects harboring A. actinomycetemcomitans of this genotype were more likely to convert to LJP than those subjects who had variants containing the full length leukotoxin promoter region (odds ratio = 22.5; 95% C.I., 2.84 < 206.66) [corrected]. These findings support the concept that highly virulent strains or clonal types of periodontal pathogens play a major role in the initiation of periodontal disease in susceptible hosts.